Problems of state and municipal social services in meeting the needs of displaced persons in Kharkiv - Євдокимова, І. А. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
This article provides an overview of the results of sociological research of problems of state and municipal social services of Kharkov to meet the needs of internally displaced persons.The author describes the activities of the state and municipal social services of the city according to the such criteria as attitude to internally displaced persons, forms of their support, additional financing, the involvement of volunteers, effectiveness and others.The article singled out the main problems that arise in the social services of the city on a personal and organizational level. The main problems that arise in dealing with displaced at the organizational level are the lack of necessary funding, lack of training, lack of a clear legal framework for working with the displaced and others. The main problems that arise on the personal level include the following: a large number of customers and the paternalistic model of behavior of internally displaced persons, "emotional burnout" of social workers and others.In addition, the author suggested directions for the further sociological studies of state and municipal social services that work with displaced in Ukraine: the information needs of social workers, effective practices of cooperation with volunteers and others.